ElemNet: Deep Learning the Chemistry of Materials From Only Elemental Composition. Issue 1 (December 2018) - Jha, Dipendra; Ward, Logan; Paul, Arindam; Liao, Wei-keng; Choudhary, Alok; Wolverton, Chris; Agrawal, Ankit
Abstract Conventional machine learning approaches for predicting material properties from elemental compositions have emphasized the importance of leveraging domain knowledge when designing model inputs. Here, we demonstrate that by using a deep learning approach, we can bypass such manual feature engineering requiring domain knowledge and achieve much better results, even with only a few thousand training samples. We present the design and implementation of a deep neural network model referred to asElemNet ; it automatically captures the physical and chemical interactions and similarities between different elements using artificial intelligence which allows it to predict the materials properties with better accuracy and speed. The speed and best-in-class accuracy ofElemNet enable us to perform a fast and robust screening for new material candidates in a huge combinatorial space; where we predict hundreds of thousands of chemical systems that could contain yet-undiscovered compounds.